Impact of orthodontic correction of dental crowding with pre-molar extraction in the anterior mandible evaluated by cone-beam computed tomography - Claudia Assunção e Alves Cardoso; Claudia Scigliano Valerio; Juliana de Carvalho Carmelo; Lizandra Gonzaga Rodrigues; Amaro Ilídio Vespasiano Silva; Flávio Ricardo Manzi (Wolters Kluwer Medknow Publications, 2022)
INTRODUCTION: To evaluate, by cone-beam computed tomography (CBCT), the change in thickness and height of the alveolar bone and interdental septum in the anterior mandible after orthodontic treatment for dental crowding using tooth extraction. MATERIAL AND METHODS: The sample consisted of 48 mandibular incisors from adult patients who presented with Class I malocclusion and required orthodontic treatment with the extraction of mandibular premolars. CBCT images were taken before starting the treatment (T1) and three months after treatment (T2). The following measurements were evaluated: width and height of the alveolar bone and the interdental septum, the distance between the cementoenamel junction and the bone ridges (F-CEJ-MBC and L-CEJ-MBC), as well as the vertical positioning and inclination of the incisor, using the Lingual Plane as the reference point. The paired Student's t-test and Pearson correlation were used with a significance level of 5%. RESULTS: A significant increase was observed in the distance L-CEJ-MBC, which shows the appearance of bone dehiscence. The degree of dental crowding was not a risk factor for the development of dehiscence. The decrease in the incisor inclination and intrusion was related to the formation of dehiscence on the lingual surface. CONCLUSION: The variation in the incisor's inclination and intrusion during the treatment of dental crowding using tooth extraction are related to the formation of bone dehiscence on its lingual surface.